PENGARUH PENAMBAHAN ABU BONGGOL JAGUNG TERHADAP KUAT TEKAN BETON K - 200 - Rasio Hepiyanto; Mohammad Arif Firdaus (Kadiri University, 2019)
Concrete is a composite material (mixture) of several materials, whose main material consists of a mixture of cement, fine aggregates, coarse aggregates, water and or without other additives with certain comparisons. This study uses ingredients added by Abu Bonggol Corn which aims to determine the effect of the addition of Corn Bonggol to the compressive strength of concrete with a percentage variation of 0%, 4%, 8%, and 12% of the weight of cement. The concrete value of 28 days of normal concrete (19.96 Mpa) 203.24 (kg / cm2) while with substitution of corn cobs ash 4% (33.04 Mpa) 336.80 (kg / cm2), 8% (30.79 MPa) ) 313.57 (kg / cm2), 12% (28.20 Mpa) 287.44 (kg / cm2). Then it can be concluded that all variants exceeding the desired target, the optimum value of substitution of corncob ash is in the 4% variant which is 33.04 Mpa, 336.80 (kg / cm2).Keywords: Concrete Quality; Testing of Concrete Compressive Strength; Corncob AshÂ Beton adalah material komposit (campuran) dari beberapa material, yang material utamanya terdiri dari campuran semen, agregat halus, agregat kasar, air dan atau tanpa aditif lain dengan perbandingan tertentu. Penelitian ini menggunakan bahan-bahan yang ditambahkan oleh Abu Bonggol Jagung yang bertujuan untuk mengetahui pengaruh penambahan Jagung Bonggol terhadap kuat tekan beton dengan variasi persentase 0%, 4%, 8%, dan 12% dari berat semen. Nilai beton normal beton 28 hari (19,96 Mpa) 203,24 (kg / cm2) sedangkan dengan substitusi abu tongkol jagung 4% (33,04 Mpa) 336,80 (kg / cm2), 8% (30,79 MPa)) 313,57 (kg / cm2), 12% (28,20 Mpa) 287,44 (kg / cm2). Maka dapat disimpulkan bahwa semua varian melebihi target yang diinginkan, nilai substitusi abu tongkol jagung yang optimal adalah pada varian 4% yaitu 33,04 Mpa, 336,80 (kg / cm2).Kata Kunci: Kualitas Beton; Pengujian Kuat Tekan Beton; Abu Tongkol Jagung.